Influence of γ phase on the magnetostructural transition and magnetocaloric properties in Ni38Co12Mn41Sn9 melt-spun ribbons - Chen, F.; Sánchez Valdés, César Fidel; Sánchez Llamazares, J.L.; Müllner, P.; Tong, Y.X.; Li, L. (2023)
In the present work, Ni38Co12Mn41Sn9 melt-spun ribbons were annealed under different conditions to make samples free of secondary γ phase precipitates or get them with various average grain sizes. A comparative study was carried out to demonstrate how γ phase formation affects the martensitic transformation (MT) and the magnetocaloric properties linked to the first-order phase transition. The γ phase significantly reduces the structural transformation temperatures, while slightly increases the thermal hysteresis. The γ phase also decreases the maximum entropy change (|ΔS|max) and the effect is more significant for smaller γ phase precipitates. As compared with those with coarse γ phase grains, the ribbons containing smaller ones possess a lower |ΔS|max but a smaller maximum magnetic hysteresis loss.